Histoiese Jesus-navorsing en evangelisasie - Schutte, P. J. W. (Hervormde teologiese studies, 1999)
Historical Jesus research and the church's vision of evangelism. The aim of this article is to demonstrate that the research results of one subject in the theological curriculum could be used in other subjects as well. In this article the results of historical Jesus research are used to facilitate a reinterpretation of the churchfs vision of evangelism. The article focuses on Jesus, subversion of conventional, cultural values, his pneumatic existence and his interaction with outcasts and elite alike. This interacion implies a redefinition of purity regulations. Specifically, the aricle elaborates on the work of Marcus Borg and Andries van Aarde as Jesus researchers. The implicaion for evangelism of Jesus' subversion of convenional values is that evangelism should not have the aim to socialize people into exising cultural paterns or values under preense of communicaing the gospel message. Evangelism should not be coercive but should rather be an invitaion to share a spiritual life. The essence of the church's message should be that all people have equal, direct and immediate access to God.